ESTIMATION OF THE CHLOROPHYLL CONTENTS OF TOBACCO INFECTED BY THE MOSAIC VIRUS BASED ON CANOPY HYPERSPECTRAL CHARACTERISTICS - D. Y. Xu; X. J. Li; Y. Q. Dou; M. Q. Liu; Y. H. Yang; J. J. Niu (Journal of Animal and Plant Sciences, 2015)
Chlorophyll content is a very important assessment index in the growing situation of crops. Estimating the chlorophyll content of tobacco accurately is an effective means of rating tobacco disease. First, field measurements were used to obtain hyper-spectral data and the chlorophyll contents of the tobacco canopy. Then, some basic data, such as the first order derivative, vegetation index, various position variables, and the area variables, were extracted from the hyper spectrum. Then, a stepwise regression analysis is combined with the above data to establish a chlorophyll estimation model of mosaic virus-infected tobacco. The results indicate that the best chlorophyll estimation model is based on position variables and area variables. The correlation coefficient of best chlorophyll content estimation model for mosaic tobacco is 0.941 and its R2 is 0.885. Therefore, it is considered that monitoring the chlorophyll content of mosaicinfected tobacco would be feasible with hyper-spectral technology. Furthermore, it could provide technical support for the scientific management and decision-making of the tobacco field.
Keywords: hyper spectrum remote sensing; tobacco mosaic disease; chlorophyll content; regression analysis; estimation